Inorganic fluorine-containing anion functionalized microporous material as well as preparation method and application thereof
By developing inorganic fluorine-containing anion functionalized microporous materials, using their rich adsorption sites and appropriate pore sizes, selective separation of ethylene/ethane and efficient capture of carbon dioxide are achieved, which solves the problems of high energy consumption and separation difficulties in the prior art, and achieves low energy consumption and high efficiency gas separation and carbon capture effects.
Patent Information
- Application Number
- CN202411727293.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The prior art has problems of high energy consumption and difficulty in separation in ethylene/ethane separation and carbon capture concentrations. In addition, traditional gas separation technology has high energy consumption and high equipment investment, making it difficult to achieve low energy consumption and efficient gas separation.
A class of inorganic fluorine-containing anion functionalized microporous materials were developed, which were synthesized by solvothermal reaction or microwave reaction. The materials had suitable pore size and abundant adsorption sites of fluorine-containing anions and azole, so as to achieve preferential adsorption of alkanes at medium and low pressures of olefins/alkanes and conduct carbon dioxide adsorption separation.
The selective separation of olefins/alkanes and efficient capture of carbon dioxide are achieved, which reduces energy consumption and improves the efficiency of the separation process. The structural design and height adjustment of the material make it have great potential in industrial applications.
Smart Images

Figure CN119570055A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous material synthesis and gas separation, and in particular to a class of inorganic fluorine-containing anion functionalized microporous materials and a preparation method and application thereof. Background Art
[0002] At present, the separation of high-purity gases and carbon capture are both popular directions in the industry. Low-carbon hydrocarbons (including ethylene) are important basic chemical raw materials and are widely used in various fields of manufacturing industries such as plastics, rubber, and masks. The demand is huge. Multi-step separation methods such as catalytic dehydrogenation are commonly used in industry. The conversion rate is limited when preparing low-carbon olefins, and a large amount of alkanes are inevitably introduced into the product. At present, the technical means commonly used to separate low-carbon olefins / alkanes in industrial production is cryogenic distillation technology. This traditional gas separation and purification technology has high energy consumption, large equipment investment, and complex process, resulting in high energy consumption and operating costs. The energy consumption of separating and removing alkanes from olefins accounts for about 0.3% of the global total energy consumption. Therefore, it is urgent to develop efficient, energy-saving, clean and environmentally friendly ethylene / ethane separation technology. Carbon capture is not only one of the key technologies for low-carbon utilization of fossil energy, but also a feasible technical solution for deep decarbonization of industries that are difficult to reduce emissions, such as steel, cement, and chemical industry. Among the current mainstream methods of CO2 capture, both cryogenic distillation and liquid absorption methods face the problem of high energy consumption. Therefore, there is an urgent need to develop new separation technologies to achieve low-energy and high-efficiency gas separation and carbon capture.
[0003] Adsorption separation technology based on porous materials does not involve phase change and is an efficient and energy-saving separation technology. This technology has the advantages of low energy consumption, low cost, simple industrial process, and high product purity. It can obtain high product purity and yield and has great potential for industrial application.
[0004] For example, the current olefin / alkane adsorption separation methods mainly include two types: target gas priority adsorption and impurity gas priority adsorption. The adsorption and desorption process of the target gas priority adsorption separation method is relatively complicated, while the impurity gas priority adsorption can directly collect high-purity target gas in one step. The process is simple and is a more ideal high-purity gas production method. For the separation and production process of olefins and alkanes, it is obviously a simpler and more efficient method to preferentially adsorb alkanes. The core of the development and breakthrough of adsorption separation technology based on porous materials lies in the design and synthesis of new and efficient porous materials, and ideally they should have high adsorption selectivity and excellent adsorption separation capabilities. Among them, porous coordination polymers such as metal-organic frameworks (MOFs), molecular sieves, covalent organic framework materials (COFs), and hydrogen-bonded organic framework materials (HOFs) have performed well in olefin and alkane separation and efficient carbon capture and have received widespread attention. For example, Zhang et al. designed and synthesized a fluorinated anion pillared material ZU-36-Ni, which is composed of metal ions Ni+ , inorganic anion GeF6 2- It can be coordinated with the organic ligand pyrazine to form an efficient separation of olefins / alkanes. Its IAST separation selectivity for ethylene / ethane (50 / 50) mixture at 298K and 1bar is 2.5 [Zhang Z, Ding Q, Cui X, et al. Fine-Tuning and Selective-Binding within an Anion-Functionalized Ultramicroporous Metal-Organic Framework for Efficient Olefin / Paraffin Separation [J]. ACS Applied Materials & Interfaces, 2020, 12 (36): 40229-35.]; Ding et al. reported an inorganic oxygen-containing anion functionalized material ZnAtzPO4. At 298K and 1bar, the equilibrium adsorption capacity of ZnAtzPO4 for ethylene is 1.92 mmol g -1 , and the selectivity for ethylene / ethane separation is 12.4 [Ding Q, Zhang Z, Yu C, et al. Exploiting equilibrium-kinetic synergetic effect for separation of ethylene and ethane in a microporous metal-organic framework [J]. Science Advances, 2020, 6 (15): eaaz4322.]. At the same time, these microporous materials have also been reported to perform well in carbon capture and have high carbon dioxide adsorption capacity. However, no one has reported the simultaneous introduction of inorganic fluorinated anions and nitrogen azole ligands to construct materials and apply them to olefin and alkane separation and carbon capture applications.
[0005] In summary, the separation of ethylene and ethane is still difficult, and alkane-preferential adsorption can directly remove alkane impurities in olefins to obtain high-purity olefin products, which is a more ideal alkane separation method. In addition, for the efficient capture of carbon dioxide, it is also urgent to develop high-performance adsorption separation materials to improve the efficiency of the separation process. Summary of the invention
[0006] In view of the above technical problems and the shortcomings in the art, the present invention provides a class of inorganic fluorine-containing anion functionalized microporous materials and their preparation methods and applications. The microporous material of the present invention has a suitable pore size (such as ), rich fluorine-containing anion and nitrogen azole adsorption sites, using them as adsorbents to achieve preferential adsorption of alkanes in olefins / alkanes at low pressures, and to achieve carbon dioxide adsorption and separation.
[0007] [1] Inorganic fluorine-containing anion functionalized microporous material, the microporous material is a polymer formed by coordination of metal ion M, inorganic fluorine-containing anion A and azole organic ligand L through solvothermal reaction; the solvothermal reaction adopts a rotary oven or microwave reaction;
[0008] The azole organic ligand L is selected from at least one of the compounds having a structure shown in any one of the following formulas (I) to (IV):
[0009]
[0010] In formula (I), R1 is selected from the following groups: -H, -NH2, -CH3;
[0011] In formula (I) and (II), R2 is independently selected from the following groups: -H, -NH2, -CH3, -COOH, -SH, -F, -Br, -Cl, -OH, -NO2, -CF3;
[0012] The metal ion M can be selected from Zn 2+ 、Ni 2+ , Cu 2+ At least one of;
[0013] The inorganic fluorine-containing anion A is selected from SiF6 2- 、GeF6 2- 、TiF6 2- ,NbOF5 2- SnF6 2- 、ZrF6 2- At least one of .
[0014] Furthermore, the pore size of the inorganic fluorine-containing anion functionalized microporous material is
[0015] Optionally, the microporous material may be a polymer formed by coordination of metal ions M, inorganic fluorine-containing anions A and azole organic ligands L in a molar ratio of (0.5-5):1:(1-10) (eg 1:1:4-8, etc.) through solvothermal reaction.
[0016] In some embodiments, the inorganic fluorine-containing anion functionalized microporous material has a rod-like microscopic morphology. Furthermore, the rod length may be 5 to 20 microns, and the rod width may be 1 to 5 microns.
[0017] [2] A method for preparing the inorganic fluorine-containing anion functionalized microporous material described in [1], comprising:
[0018] A mixed solution containing metal ions M, inorganic fluorine-containing anions A and azole organic ligands L is prepared, and a crude target product is obtained by solvent thermal reaction. The obtained crude target product is washed, degassed and activated to obtain the inorganic fluorine-containing anion functionalized microporous material;
[0019] The solvent thermal reaction adopts a rotary oven or a microwave reaction.
[0020] The method for preparing the inorganic fluorine-containing anion functionalized microporous material described in [1] of the present invention is a solvent thermal reaction synthesis method, preferably a microwave reaction synthesis method.
[0021] [2] The method described in claim 1, wherein the molar ratio of the metal ion M, the inorganic fluorine-containing anion A and the azole organic ligand L in the mixed solution can be (0.5-5):1:(1-10), for example, 1:1:4-8.
[0022] [2] The method described above, wherein the solvent in the mixed solution may be water and an organic solvent. Further, the organic solvent may be one or more of methanol, n-butanol, ethanol, and N,N-dimethylformamide. The volume ratio of water to the organic solvent in the mixed solution may be (5:1) to (1:5), such as 1:1.
[0023] [2] The temperature of the solvothermal reaction may be 100 to 200°C, and further may be 160 to 180°C;
[0024] In some embodiments, the method described in [2], the solvent thermal reaction can be carried out in a rotary oven, and the corresponding reaction time can be 48 to 72 hours.
[0025] In some embodiments, the method described in [2], the solvent thermal reaction can be carried out by microwave reaction, the microwave reaction time can be 0.5 to 3 hours, further can be 0.5 to 1.5 hours, such as 1 hour, etc., and the microwave power is preferably not more than 250W, such as 100W, etc.
[0026] [2] The washing agent used in the washing may be water and methanol.
[0027] [2] The method described in claim 2, wherein the degassing activation conditions may include: vacuuming at 50 to 120°C (e.g., 100°C), and the degassing activation time may be 8 to 24 hours, and further may be 10 to 12 hours.
[0028] The inorganic fluorine-containing anion functionalized microporous material described in [1] can be applied in the field of gas adsorption.
[0029] [3] Application of the inorganic fluorine-containing anion functionalized microporous material according to [1] in selective adsorption separation of olefins / alkanes. The application can use the inorganic fluorine-containing anion functionalized microporous material as an adsorbent for adsorption separation of mixed gases containing olefins / alkanes. The olefins may include ethylene, etc. The alkanes may include ethane, etc.
[0030] [3] In the application described above, the volume ratio of the olefin component to the alkane component in the olefin / alkane-containing mixed gas may be (1:99) to (99:1); the adsorption temperature may be -50 to 100°C, and the adsorption pressure may not exceed 10 bar.
[0031] [3] In the application described above, the inorganic fluorine-containing anion functionalized microporous material can preferentially adsorb alkanes at a low pressure of 0 to 0.8 bar (e.g., 0.15 bar, etc.).
[0032] [4] Use of the inorganic fluorine-containing anion functionalized microporous material according to [1] in carbon dioxide adsorption. The carbon dioxide adsorption temperature may be -50 to 100°C, and the carbon dioxide adsorption pressure may not exceed 10 bar.
[0033] [5] A method for separation of olefins / alkanes by adsorption, wherein the inorganic fluorine-containing anion functionalized microporous material described in [1] is used as an adsorbent, and the adsorbent is contacted with a mixed gas containing olefins / alkanes to achieve selective adsorption separation of olefins and alkanes. The mixed gas may be a mixed gas containing ethylene / ethane.
[0034] The method described in [5] can refer to the application described in [3] for further specific selection and optimization of the technical solution.
[0035] [6] A method for adsorbing carbon dioxide using the inorganic fluorine-containing anion functionalized microporous material described in [1].
[0036] The method described in [6] can refer to the application described in [4] for further specific selection and optimization of the technical solution.
[0037] [1] The inorganic fluorine-containing anion functionalized microporous material can be amorphous particles or spherical or cylindrical particles after molding.
[0038] The present invention can realize the construction of microporous materials and the regulation of functional sites by introducing inorganic fluorine-containing anions and changing the type and structure of azole ligands, thereby obtaining abundant anion and azole adsorption sites; and realize effective recognition and differentiation of olefin or alkane molecules through the difference in pore size and force, wherein the inorganic fluorine-containing anions and azole sites differentiate olefins from alkanes through electronic effects, thereby realizing the selective separation of ethylene / ethane.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1) The inorganic fluorine-containing anion functionalized microporous material prepared by the present invention has excellent structural design and high adjustability, high density of inorganic fluorine-containing anions and nitrogen azole functional sites, and the pore size of the material can be precisely controlled according to the type of ligand.
[0041] 2) The inorganic fluorine-containing anion functionalized microporous material designed and synthesized by the present invention has good recognition and differentiation capabilities for ethylene, ethane, propylene and propane, and can effectively achieve preferential adsorption of alkanes and selective separation of olefins / alkanes. The high density of inorganic fluorine-containing anions and nitrogen azole functional sites is conducive to the selective recognition of gases, and it also has a certain capture ability for carbon dioxide.
[0042] 3) The preferred preparation method of the present invention is microwave synthesis, which is green, simple and rapid, and the anion-functionalized azole-based microporous coordination polymer material is easy to prepare. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is the adsorption isotherm diagram of ethylene and ethane of ZnAtzSiF6 of Example 1 at 298K;
[0044] Figure 2 is the ethylene / ethane IAST separation selectivity calculated for ZnAtzSiF6 at 298K in Example 1;
[0045] Figure 3 is the ZnAtzSiF6 powder X-ray diffraction (PXRD) pattern of Example 1;
[0046] Figure 4 , Figure 5 This is a scanning electron microscope (SEM) photograph of ZnAtzSiF6 of Example 1;
[0047] Figure 6 is the adsorption isotherm diagram of ethylene and ethane of ZnAtzGeF6 of Example 2 at 298K;
[0048] Figure 7 is the X-ray diffraction pattern of ZnAtzGeF6 powder of Example 2;
[0049] Figure 8 is the adsorption isotherm diagram of ethylene and ethane of ZnAttzSiF6 of Example 3 at 298K;
[0050] Fig. 9 is the adsorption isotherm diagram of ethylene and ethane of ZnAtzTiF6 of Example 4 at 298K;
[0051] Fig.10It is the adsorption isotherm diagram of carbon dioxide at 298K for ZnAtzSiF6 of Example 1, ZnAtzGeF6 of Example 2, ZnAttzSiF6 of Example 3, and ZnAtzTiF6 of Example 4. DETAILED DESCRIPTION
[0052] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0053] Example 1
[0054] According to the metal ion Zn 2+ 、Fluorinated SiF6 2- Zinc hexafluorosilicate hexahydrate (0.5 mmol) and 3-amino-1,2,4-triazole (4 mmol) were dissolved in a mixed solution of methanol (5 mL) and water (5 mL) with an organic ligand in a molar ratio of 1:1:8, and then transferred to a 35 mL microwave reaction bottle, and reacted at 100 W microwave power and 180 ° C for 1 h to obtain a white solid precipitate. The precipitate was filtered, washed with water and methanol, and finally vacuum degassed and activated at 100 ° C for 10 hours to obtain an activated hexafluorosilicic acid functionalized microporous material, which can be used as an adsorbent and is named ZnAtzSiF6.
[0055] Example 1 The adsorption isotherms of ethylene and ethane at 298K are as follows: Figure 1 As shown; Example 1 adsorbent calculated at 298K ethylene / ethane IAST separation selectivity is as follows Figure 2 As shown; the PXRD pattern of the adsorbent of Example 1 is as shown Figure 3 As shown; the SEM photo of the adsorbent in Example 1 is as shown Figure 4 , Figure 5 As shown, the adsorbent has a rod-like microscopic morphology of 10.44 μm in length and 2.42 μm in width; the adsorption isotherm of carbon dioxide by the adsorbent of Example 1 at 298 K is as follows Fig.10 shown.
[0056] The hexafluorosilicic acid functionalized microporous material has a carbon dioxide adsorption capacity of 2.50 mmol / g at 1 bar. -1 The adsorption capacity of ethylene at 1 bar is 1.55 mmol g -1 The adsorption capacity of ethane is 1.57 mmol g -1 The selectivity of ethane / ethylene (10 / 90 volume ratio) is 1.83 at 0.15 bar, and it exhibits the property of preferentially adsorbing alkanes under low pressure.
[0057] Example 2
[0058] According to the metal ion Zn2+ 、Fluoride-containing GeF6 2- Zinc nitrate hexahydrate (0.5 mmol), ammonium hexafluorogermanate (0.5 mmol) and 3-amino-1,2,4-triazole (4 mmol) were dissolved in a mixed solution of methanol (5 mL) and water (5 mL) in a molar ratio of 1:1:8 with an organic ligand, and then transferred to a 35 mL microwave reaction bottle, and reacted at 100 W microwave power and 180 ° C for 1 h to obtain a white solid precipitate. The precipitate was filtered, washed with water and methanol, and finally vacuum degassed and activated at 100 ° C for 10 hours to obtain an activated hexafluorogermanic acid functionalized microporous material, which can be used as an adsorbent and is named ZnAtzGeF6.
[0059] Example 2 The adsorption isotherms of ethylene and ethane at 298K are as follows: Figure 6 As shown; the PXRD pattern of the adsorbent of Example 2 is as shown Figure 7 As shown; the adsorption isotherm of carbon dioxide by the adsorbent of Example 2 at 298K is as follows Fig.10 shown.
[0060] The hexafluorogermanic acid functionalized microporous material has a carbon dioxide adsorption capacity of 2.27 mmol / g at 1 bar. -1 The adsorption capacity of ethylene at 1 bar is 1.45 mmol g -1 The adsorption capacity of ethane is 1.48 mmol g -1 At 0.15 bar, the selectivity of ethane / ethylene (10 / 90 volume ratio) is 1.78, showing the property of preferential adsorption of alkanes.
[0061] Example 3
[0062] According to the metal ion Zn 2+ 、Fluorinated SiF6 2- Zinc hexafluorosilicate hexahydrate (0.5 mmol) and 5-aminotetrazole (4 mmol) were dissolved in a mixed solution of methanol (5 mL) and water (5 mL) at a molar ratio of 1:1:8 and then transferred to a 35 mL microwave reaction bottle and reacted at 100 W microwave power and 180 ° C for 1 h to obtain a white solid precipitate. The precipitate was filtered, washed with water and methanol, and finally vacuum degassed and activated at 100 ° C for 10 hours to obtain an activated hexafluorosilicic acid functionalized microporous material, which can be used as an adsorbent and is named ZnAttzSiF6.
[0063] Example 3 The adsorption isotherms of ethylene and ethane at 298K are as follows: Figure 8 As shown, the adsorption isotherm of carbon dioxide by the adsorbent of Example 3 at 298K is as follows Fig.10 As shown. Its adsorption capacity of carbon dioxide at 1 bar is 2.16mmolg-1 The adsorption capacity of ethylene at 1 bar is 1.30 mmol g -1 The adsorption capacity of ethane is 1.36 mmol g -1 The selectivity of ethane / ethylene (10 / 90 volume ratio) at 0.15 bar is 2.07, showing the property of preferential adsorption of alkanes.
[0064] Example 4
[0065] According to the metal ion Zn 2+ 、Fluoride-containing TiF6 2- Basic zinc carbonate (1 mmol), ammonium hexafluorotitanate (1 mmol) and 3-amino-1,2,4-triazole (4 mmol) were dissolved in a mixed solution of methanol (5 mL) and water (5 mL) in a molar ratio of 1:1:4 with an organic ligand, and then transferred to a 35 mL microwave reaction bottle, and reacted at 100 W microwave power and 180 ° C for 1 h to obtain a white solid precipitate. The precipitate was filtered, washed with water and methanol, and finally vacuum degassed and activated at 100 ° C for 10 hours to obtain an activated hexafluorotitanic acid functionalized microporous material, which can be used as an adsorbent and is named ZnAtzTiF6.
[0066] Example 4 The adsorption isotherms of ethylene and ethane at 298K are as follows: Fig. 9 As shown, the adsorption isotherm of carbon dioxide by the adsorbent of Example 4 at 298K is as follows Fig.10 As shown. Its adsorption capacity of carbon dioxide at 1 bar is 1.78mmolg -1 The adsorption capacity of ethylene at 1 bar is 1.22 mmol g -1 The adsorption capacity of ethane is 1.26 mmol g -1 At 298K and 0.15bar, the selectivity of ethane / ethylene (10 / 90 volume ratio) is 1.49, showing the property of preferential adsorption of alkanes.
[0067] Example 5
[0068] According to the metal ion Cu 2+ 、Fluorinated SiF6 2- Copper hexafluorosilicate (0.5 mmol) and 3-amino-1,2,4-triazole (4 mmol) were dissolved in a mixed solution of methanol (5 mL) and water (5 mL) with an organic ligand in a molar ratio of 1:1:8, and then transferred to a 35 mL microwave reaction bottle, and reacted at 100 W microwave power and 180 ° C for 1 h to obtain a white solid precipitate. The precipitate was filtered, washed with water and methanol, and finally vacuum degassed and activated at 100 ° C for 10 hours to obtain an activated hexafluorosilicic acid functionalized microporous material, which can be used as an adsorbent and is named CuAtzSiF6.
[0069] Example 5 The adsorption capacity of ethylene by the adsorbent at 298K and 1 bar is 1.35 mmol g -1 The adsorption capacity of ethane is 1.39 mmol g -1 The selectivity of ethane / ethylene (10 / 90 volume ratio) at 0.15 bar is 1.44, and ethane is preferentially adsorbed when applied to ethylene / ethane separation.
[0070] Example 6
[0071] According to the metal ion Zn 2+ 、Fluorinated SiF6 2- Zinc hexafluorosilicate hexahydrate (0.5 mmol) and 3-amino-5-carboxylic acid-1,2,4-triazole (4 mmol) were dissolved in a mixed solution of methanol (5 mL) and water (5 mL) in a molar ratio of 1:1:8 with an organic ligand, and then transferred to a 35 mL microwave reaction bottle, and reacted at 100 W microwave power and 180 ° C for 1 h to obtain a white solid precipitate. The precipitate was filtered, washed with water and methanol, and finally vacuum degassed and activated at 100 ° C for 10 hours to obtain an activated hexafluorosilicic acid functionalized microporous material, which can be used as an adsorbent and is named ZnAtzcSiF6.
[0072] Example 6 The adsorption capacity of ethylene by the adsorbent at 298K and 1 bar is 1.41 mmol g -1 The adsorption capacity of ethane is 1.48 mmol g -1 The selectivity of ethane / ethylene (10 / 90 volume ratio) at 0.15 bar is 1.51. When applied to ethylene / ethane separation, ethane is preferentially adsorbed selectively.
[0073] Example 7
[0074] According to the metal ion Zn 2+ 、Fluorinated SiF6 2- Zinc hexafluorosilicate hexahydrate (1 mmol) and 4-(4H-1,2,4-triazol-4-yl)-4H-1,2,4-triazole (4 mmol) were dissolved in a mixed solution of methanol (5 mL) and water (5 mL) with an organic ligand in a molar ratio of 1:1:4, and then transferred to a 35 mL microwave reaction bottle, and reacted at 100 W microwave power and 180 ° C for 1 h to obtain a white solid precipitate. The precipitate was filtered, washed with water and methanol, and finally vacuum degassed and activated at 100 ° C for 10 hours to obtain an activated hexafluorosilicic acid functionalized microporous material, which can be used as an adsorbent and is named ZnBtzSiF6.
[0075] Example 7 The adsorption capacity of ethylene by the adsorbent at 298K and 1 bar is 1.36 mmol g -1The adsorption capacity of ethane is 1.42 mmol g -1 The selectivity of ethane / ethylene (10 / 90 volume ratio) at 0.15 bar is 1.38. When applied to ethylene / ethane separation, ethane is preferentially adsorbed selectively.
[0076] Example 8
[0077] According to the metal ion Ni 2+ 、NbOF5 containing fluoride 2- Nickel pentafluoroniobate (1 mmol) and 3-amino-1,2,4-triazole (4 mmol) were dissolved in a mixed solution of methanol (5 mL) and water (5 mL) with an organic ligand in a molar ratio of 1:1:4, and then transferred to a 35 mL microwave reaction bottle, and reacted at 100 W microwave power and 180 ° C for 1 h to obtain a white solid precipitate. The precipitate was filtered, washed with water and methanol, and finally vacuum degassed and activated at 100 ° C for 10 hours to obtain an activated pentafluoroniobate functionalized microporous material, which can be used as an adsorbent and is named NiAtzNbOF5.
[0078] Example 8 The adsorption capacity of ethylene by the adsorbent at 298K and 1 bar is 1.31 mmol g -1 The adsorption capacity of ethane is 1.38 mmol g -1 The selectivity of ethane / ethylene (10 / 90 volume ratio) at 0.15 bar is 1.35. When applied to ethylene / ethane separation, ethane is preferentially adsorbed selectively.
[0079] Comparative Example 1
[0080] Comparative Example 1 is a material reported to be synthesized using a microwave reactor (Science 353, 141-144 (2016).) SIFSIX-2-Cu-i, a microporous material composed of metal ions, fluoride-containing acid radicals and pyridine compounds, which differs from Example 2 in the metal ions and organic ligands. The ethylene adsorption capacity of the microporous material adsorbent in Comparative Example 1 at 298K and 1 bar is 2.53 mmol g -1 The adsorption capacity of ethane is 1.81 mmol g -1 Compared with Example 2, it cannot achieve the separation of alkanes and alkenes under low pressure (0-0.8 bar) and does not have the characteristic of preferentially adsorbing alkanes.
[0081] Comparative Example 2
[0082] Comparative Example 2 is an inorganic fluorine-containing microporous anion material SIFSIX-3-Zn reported in the literature (CrystEngComm 22 (2020) 2649-2655.), which differs from Example 2 in that its organic ligand is pyrazine. The only reported ethylene adsorption capacity of the inorganic fluorine-containing microporous anion material adsorbent in Comparative Example 2 is 2.24 mmol g at 298 K. -1 Compared with Example 2, it is not possible to separate alkanes from alkenes and does not have the characteristic of preferentially adsorbing alkanes.
[0083] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. Inorganic fluorine-containing anion functionalized microporous material, characterized in that: The microporous material is a polymer formed by coordination of metal ions M, inorganic fluorine-containing anions A and azole organic ligands L through solvent thermal reaction; the solvent thermal reaction adopts a rotary oven or microwave reaction; The azole organic ligand L is selected from at least one of the compounds having a structure shown in any one of the following formulas (I) to (IV): In formula (I), R1 is selected from the following groups: -H, -NH2, -CH3; In formula (I) and (II), R2 is independently selected from the following groups: -H, -NH2, -CH3, -COOH, -SH, -F, -Br, -Cl, -OH, -NO2, -CF3; The metal ion M is selected from Zn 2+ 、Ni 2+ , Cu 2+ At least one of; The inorganic fluorine-containing anion A is selected from SiF6 2- 、GeF6 2- 、TiF6 2- ,NbOF5 2- SnF6 2- 、ZrF6 2- At least one of .
2. The inorganic fluorine-containing anion functionalized microporous material according to claim 1, characterized in that: The pore size of the inorganic fluorine-containing anion functionalized microporous material is The inorganic fluorine-containing anion functionalized microporous material is a polymer formed by coordination of metal ions M, inorganic fluorine-containing anions A and azole organic ligands L in a molar ratio of (0.5-5):1:(1-10) through solvent thermal reaction.
3. A method for preparing the inorganic fluorine-containing anion functionalized microporous material according to claim 1 or 2, characterized in that: include: A mixed solution containing metal ions M, inorganic fluorine-containing anions A and azole organic ligands L is prepared, and a crude target product is obtained by solvent thermal reaction. The obtained crude target product is washed, degassed and activated to obtain the inorganic fluorine-containing anion functionalized microporous material; The solvent thermal reaction adopts a rotary oven or a microwave reaction.
4. The method according to claim 3, characterized in that In the mixed solution, the molar ratio of metal ion M, inorganic fluorine-containing anion A and azole organic ligand L is (0.5-5):1:(1-10); The solvent in the mixed liquid is water and an organic solvent; The volume ratio of water to organic solvent in the solvent of the mixed solution is (5:1) to (1:5); The organic solvent is one or more of methanol, n-butanol, ethanol and N,N-dimethylformamide.
5. The method according to claim 3, characterized in that: The temperature of the solvothermal reaction is 100 to 200°C, further 160 to 180°C; The solvent thermal reaction adopts a rotary oven, and the corresponding reaction time is 48 to 72 hours, or the solvent thermal reaction adopts a microwave reaction, and the microwave reaction time is 0.5 to 3 hours, further 0.5 to 1.5 hours, and the microwave power does not exceed 250W; The washing agents used in the washing are water and methanol; The degassing and activation conditions include: vacuuming at 50-120° C., and the degassing and activation time is 8-24 hours.
6. Use of the inorganic fluorine-containing anion functionalized microporous material according to claim 1 or 2 in selective adsorption and separation of olefins / alkanes.
7. The use according to claim 6, characterized in that: The inorganic fluorine-containing anion functionalized microporous material is used as an adsorbent for the adsorption separation of mixed gases containing olefins / alkanes; The volume ratio of the olefin component to the alkane component in the olefin / alkane-containing mixed gas is (1:99) to (99:1); the adsorption temperature is -50 to 100° C., and the adsorption pressure does not exceed 10 bar; The olefin comprises ethylene; The alkane includes ethane.
8. The use according to claim 6, characterized in that: The inorganic fluorine-containing anion functionalized microporous material preferentially adsorbs alkanes at a low pressure of 0 to 0.8 bar.
9. Use of the inorganic fluorine-containing anion functionalized microporous material according to claim 1 or 2 in carbon dioxide adsorption.
10. The use according to claim 9, characterized in that: The carbon dioxide adsorption temperature is -50 to 100°C, and the carbon dioxide adsorption pressure does not exceed 10 bar.
Citation Information
Patent Citations
Metal organic framework, production and use thereof
CN105051269A
Preparation method of ultramicroporous metal organic framework and application of ultramicroporous metal organic framework in adsorption separation of propylene and propane
CN116622076A